1995
DOI: 10.1093/nar/23.21.4391
|View full text |Cite
|
Sign up to set email alerts
|

Tmstudies of a tertiary structure from the human hepatitis delta agent which functionsin vitroas a ribozyme control element

Abstract: Viroids and other circular subviral RNA pathogens, such as the hepatitis delta agent, use a rolling circle replication cycle requiring an intact circular RNA. However, many infectious RNAs have the potential to form self-cleavage structures, whose formation must be controlled in order to preserve the circular replication template. The native structure of delta RNA contains a highly conserved element of local tertiary structure which is composed of sequences partially overlapping those needed to form the self-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Our laboratory has worked out techniques for producing specific UV crosslinks in RNA molecules at sites of preexisting local tertiary structure (Branch et al 1985a(Branch et al , 1989c, isolating the RNAs containing them by altered behavior on polyacrylamide gels, and their specific regions by partial RNase T1 digestion (Branch et al 1985b(Branch et al , 1989c, and mapping their exact positions in the RNA sequence (Branch et al 1989a(Branch et al , 1989b(Branch et al , 1989c(Branch et al , 1990aLyons et al 2001). For antigenomic HDV, a transcript containing the conserved domain, spanning residues 482-963 (shown in Fig.…”
Section: Antigenomic Hdv Has a Tertiary Structural Element In The Conmentioning
confidence: 99%
See 3 more Smart Citations
“…Our laboratory has worked out techniques for producing specific UV crosslinks in RNA molecules at sites of preexisting local tertiary structure (Branch et al 1985a(Branch et al , 1989c, isolating the RNAs containing them by altered behavior on polyacrylamide gels, and their specific regions by partial RNase T1 digestion (Branch et al 1985b(Branch et al , 1989c, and mapping their exact positions in the RNA sequence (Branch et al 1989a(Branch et al , 1989b(Branch et al , 1989c(Branch et al , 1990aLyons et al 2001). For antigenomic HDV, a transcript containing the conserved domain, spanning residues 482-963 (shown in Fig.…”
Section: Antigenomic Hdv Has a Tertiary Structural Element In The Conmentioning
confidence: 99%
“…Portions of the antigenomic RNA containing the crosslinked site and flanking sequences, along with the UVcrosslinkable site in the HDV genomic RNA (Branch et al 1990a), are shown in Figure 2. After adjusting their orientations to facilitate comparison, they reveal a number of interesting similarities.…”
Section: Comparison Of Uv-sensitive Structural Elements In Hdvmentioning
confidence: 99%
See 2 more Smart Citations
“…Within these 25 bases, only a single mutation (at C-13) has been reported in sequenced isolates of the delta agent (41). During the replication cycle, the ribozyme sequences are constrained by factors in addition to those directly related to their catalytic capability; such as their ability to function as templates for replication, which may impose sequence restrictions (42); ability to form the rodlike structure (9); and their ability to generate the UV-sensitive tertiary structure (43,44) proposed as a control element for the genomic ribozyme (45,46). In our current in vitro study, in which none of these factors had an effect, the ranking of nucleotides from the least conserved to the most conserved was as follows: (the number of clones with a mutation at a particular position is given in parenthesis): G (47), nucleotides contributing to tertiary structure are known to be highly conserved.…”
Section: Sequence Analysismentioning
confidence: 99%